2022
DOI: 10.1096/fj.202200872r
|View full text |Cite
|
Sign up to set email alerts
|

Modeling ascending Ureaplasma parvum infection through the female reproductive tract using vagina‐cervix‐decidua‐organ‐on‐a‐chip and feto‐maternal interface‐organ‐on‐a‐chip

Abstract: Genital mycoplasmas can break the cervical barrier and cause intraamniotic infection and preterm birth. This study developed a six-chamber vagina-cervixdecidua-organ-on-a-chip (VCD-OOC) that recapitulates the female reproductive tract during pregnancy with culture chambers populated by vaginal epithelial cells, cervical epithelial and stromal cells, and decidual cells. Cells cultured in VCD-OOC were characterized by morphology and immunostaining for cell-specific markers.We transferred the media from the decid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 71 publications
3
12
0
Order By: Relevance
“…Studies about U. parvum have reported that they have poor immunogenicity, does not trigger a massive inflammatory response in human samples, and does not promote PTB in mouse models, which could be explained by this specie being a commensal of rodents, resulting in an immune response that may be different compared to humans 5,11,14 . Using the FMi‐OOC model, we tested the ascending infection of U. parvum and its pathogenic properties on the FMi.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies about U. parvum have reported that they have poor immunogenicity, does not trigger a massive inflammatory response in human samples, and does not promote PTB in mouse models, which could be explained by this specie being a commensal of rodents, resulting in an immune response that may be different compared to humans 5,11,14 . Using the FMi‐OOC model, we tested the ascending infection of U. parvum and its pathogenic properties on the FMi.…”
Section: Discussionmentioning
confidence: 99%
“…These data support the systematic review and prior reports using fetal membrane explants and organ-on-a-chip devices. 5,10,14…”
Section: Parvummentioning
confidence: 99%
See 2 more Smart Citations
“…It contributes to an extreme rise in the frequency of gunshot wounds resulting in severe destruction of abdominal organs (most often the small intestine at 50 %, the large intestine at 40 %, the liver at 40 %, and the intra-abdominal vascular system at 30 %), which is accompanied by peritonitis and the further development of different complications (anastomotic leakage, formation of abscesses, repeated bleeding, etc.). Such conditions require repeated surgical interventions, which contribute to the formation of postoperative ventral hernias [34,36,37,38]. The surgical management of ventral hernias is challenging due to severe adhesion in the abdominal cavity (irrespective of the time period since the injury and the last surgical interventions), the difficulties in closing massive defects of the muscle-aponeurotic component of the anterior abdominal wall, contracture of the anterior abdominal wall, and the development of the abdominal compartment syndrome in the postoperative period.…”
mentioning
confidence: 99%